Design and Development of a Vertical-Shaft Organic Waste Chopper Machine with a Top-Mounted Agitator - Herry Susanto; Yefri Chan; Juan Pratama; Rolan Siregar; Rio Ferdiansyah; Hidayat Mustofa; Muhammad Fauzan Mubarok (Jurnal Rekayasa Mesin, 2026)
Conventional organic waste chopping machines predominantly utilize horizontal shaft configurations, which are highly susceptible to asymmetric load distribution and present ergonomic challenges during maintenance. As an innovative solution, this study presents the conceptual design of a vertical-shaft chopping machine integrated with a hydraulic-actuated top-head system to enhance the efficiency of particle size reduction. The scope of this research is strictly confined to theoretical mathematical modeling and numerical simulations. The design process complies with the ASME B106.1M standard for transmission shafts and EN 13683 for operational safety parameters, excluding experimental fabrication. A comprehensive analysis was conducted on three primary materials—Mild Steel (MS), Stainless Steel 304 (SS 304), and Stainless Steel 316L (SS 316L)—under fluctuating waste loads ranging from 10 kg to 35 kg. The analytical results demonstrate several crucial findings: the minimum safe shaft diameter ranges from 16 mm (utilizing SS 316L at a 10 kg load) to 28 mm (utilizing MS and SS 304 at a 35 kg load). Furthermore, the agitator's power requirement exhibits a strictly linear increase corresponding to the applied load (from 1.34 kW to 4.68 kW), whereas the hydraulic system operates efficiently with a constant power profile of 0.25 kW. Overall, the vertical shaft configuration significantly promotes symmetrical force distribution, while the hydraulic system ensures safe and immediate access to the chopping chamber. The proposed design demonstrates substantial structural, operational, and ergonomic advantages, establishing a robust theoretical foundation for future development and experimental fabrication.